Relationship between trees and cattle in ponderosa pine - R Pieper; H Biswell (California Agriculture, 1961)
Multiple-use management of wildlands becomes increasingly important as population pressure rises in California. Certain areas are capable of producing several products for maximum returns. In some cases several uses are compatible on the same area, while in others conflicts develop. Before any cultural practices are widely applied on areas which have a potential for multiple-use management, the effects of such practices must be studied.